Evaluation of ELISA BP180 and BP230 Autoantibodies in Blister Fluid and Serum in the Diagnosis of Bullous Pemphigoid - Harish Nagarajan; Krishnaswamy Mahadevan; Reena Rai; Appalaraju Boppe (Wolters Kluwer Medknow Publications, 2023)
Bullous pemphigoid (BP) is a chronic subepidermal immunobullous disorder. Studies have demonstrated the presence of antibasement membrane zone antibodies (BP180 & BP230) in the blister fluid using enzyme-linked immunosorbent assay (ELISA). To detect and compare BP 180 and BP 230 autoantibodies in the blister fluid and serum of patients with BP by ELISA method. A total of 30 patients diagnosed as BP and not on treatment were included in the study. Blister fluid and serum were subjected to ELISA, and the results were compared. The sensitivity of ELISA BP 180 was found to be 95.8% in the blister fluid and 88.4% in the serum. The sensitivity of ELISA BP 230 in the blister fluid and serum was 20% and 16.6%, respectively. Association between ELISA antibodies done in blister and serum was analysed using Chi-square test and found to be statistically significant with P value <0.05. Blister fluid is an effective alternative to the serum in detecting BP 180 and BP 230 antibodies, especially in uncooperative and elderly patients with poor venous access.